'Thin people … they're healthy': young children's understanding of body weight change. Issue 5 (23rd October 2015) - Baxter, S. L.; Collins, S. C.; Hill, A. J.
Summary: Background: While research has investigated negative stereotyping of fat body shapes, little has focused on young children's understanding of the mechanisms, motivations and consequences of weight change. Objectives: To investigate children's understanding of how weight change is achieved, people's motivation for weight change, and the consequences of weight loss or weight gain. Methods: One hundred children (mean age 5.2, 38 girls) read a book in which one of the main characters (male/female according to the child's sex) was either healthy weight or overweight. Afterwards, this character was described as gaining or losing weight, and drawings which depicted the child in the story as either healthy weight or overweight were presented to the child and discussed. An audio‐recorded semi‐structured interview followed and transcripts were analysed using thematic analysis. Results: Nearly all children described the weight/shape change and attributed this to food more frequently than exercise. Weight loss was viewed positively and both motivations and consequences grouped under two master themes (physical and social reasons). No clear gender differences were observed in these responses. Conclusions: Talking with 5‐year‐olds showed them to be observant and knowledgeable, especially about motivations for and consequences of weight change. For those working to improve children's health literacy, this suggests receptiveness to early and fact‐based education.